The secrets of haji and the time of Iyts performance in the light Maqasid : contemporary Caess - Hendaoui, Hassan Ben Brahim (s.n, 2012)
Hajj is a very great Islamic ritual. It is an ideal demonstration of faith in which diverse groups of every race, class, and nationality join together at a given time and in a specific place. They repeatedly recite a single call, and proclaim the same slogan. They gather for one purpose. During Hajj, Muslims witness the most excellent example of equality, submissiveness, and human brotherhood. This is accomplished by removing the outer difference and donning the dress of unity Ihram